PERSEPSI MAHASISWA UNIVERSITAS SILIWANGI MENGENAI PENGGUNAAN E-WALLET (SHOPEE PAY) SEBAGAI ALAT PEMBAYARAN NON TUNAI - Ai Yuli Mulyani; Selli Rachmawati Sabanni; Alma Nabila (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine student perceptions of Siliwangi University regarding the use of e-wallet (Shopee Pay) as a non-cash payment instrument. The research method used is descriptive qualitative research. The data collection technique is by means of a survey in the form of a questionnaire instrument which is then distributed via google form. Simple random sample was used as a sampling technique of 35 respondents. The indicators used to see the perception are the perception of convenience, the perception of usefulness or benefit, and the last is the perception of risk. This study shows the results that perceived convenience shows 97.85% of students agree that e-wallet (Shopee Pay) provides many conveniences, perceptions of usefulness or benefits show 95.23% of students provide benefits in transaction activities, risk perceptions show 68% of student responses regarding e-wallet (Shopee Pay) is low risk. Judging from the interest in transactions, it shows that 92% of students are interested in transacting via e-wallet in the form of Shopee Pay. Hence, the use of e-wallet in Siliwangi University students is influenced by these three perceptions.